Switching from sulphonylurea to a sodium‐glucose cotransporter2 inhibitor in the fasting month of Ramadan is associated with a reduction in hypoglycaemia. Issue 6 (22nd March 2016) - Wan Seman, W. J.; Kori, N.; Rajoo, S.; Othman, H.; Mohd Noor, N.; Wahab, N. A; Sukor, N.; Mustafa, N.; Kamaruddin, N. A.
Abstract : The aim of the present study was to assess the hypoglycaemia risk and safety of dapagliflozin compared with sulphonylurea during the fasting month of Ramadan. In this 12‐week, randomized, open‐label, two‐arm parallel group study, 110 patients with type 2 diabetes who were receiving sulphonylurea and metformin were randomized either to receive 10 mg (n = 58) of dapagliflozin daily or to continue receiving sulphonylurea (n = 52). The primary outcome was to compare the effects of dapagliflozin and sulphonylurea on the proportions of patients with at least one episode of hypoglycaemia during Ramadan, as well as to assess the safety of dapagliflozin when used to treat patients observing Ramadan. A lower proportion of patients had reported or documented hypoglycaemia in the dapagliflozin group than in the sulphonylurea group: 4 (6.9%) versus 15 (28.8%); p = 0.002. The relative risk of any reported or documented hypoglycaemia in the 4th week of Ramadan was significantly lower in the dapagliflozin group: RR=0.24, 95%CI: 0.09, 0.68; p=0.002. No significance differences were observed between the two groups regarding postural hypotension (13.8 vs 3.8%; p = 0.210) or urinary tract infections (10.3 vs 3.8%; p = 0.277). In conclusion, fewer patients exhibited hypoglycaemia in the dapagliflozin group than in the sulphonylurea group.